THE SEMANTIC EVOLUTION OF ENGLISH WORDS WITHIN THE CONTEXT OF TECHNOLOGY AND SOCIETAL INFLUENCES - Eshankulov Ravshan Takhirovich (Web of Journals Publishing, 2023)
This article delves into the dynamic landscape of linguistic evolution by investigating the semantic changes of English words within the intricate interplay of technology and societal influences. Grounded in the rich traditions of sociolinguistics, corpus linguistics, and digital discourse analysis, our study focuses on the semantic evolution of high-frequency words within diverse online forums. Drawing on historical perspectives and established linguistic theories, we explore how the meanings of words adapt in response to technological advancements and shifting societal norms. Through a comprehensive analysis of linguistic patterns, frequency shifts, and contextual usage, we identify subtle nuances and emergent trends in the semantic evolution of English words. Noteworthy case studies shed light on specific words that have undergone remarkable transformations. Our findings contribute to the ongoing scholarly discourse surrounding linguistic evolution, bridging gaps in the current literature and providing insights into the complex relationship between language, technology, and society. As we unravel the intricacies of semantic adaptation, our study not only enhances our understanding of linguistic change but also holds implications for communication strategies, technological development, and the broader cultural landscape.
Keywords: lexical shifts, technological onslaught, cultural dynamics, communication paradigms, innovation jargon, semantic adaptation, language pioneers, digital vernacular, sociolinguistic trends, expressive resilience.